How do adolescent clients experience power in person-centred therapy relationships? An interpretative phenomenological analysis - Cook, David (2018)
Background: Person-centred therapy aims to help clients actualise their own power within a relationship characterised by certain conditions. When working with adolescents, the developmental needs of the client and the power difference between client and therapist may present additional barriers to this. To understand the implications of this we need to view the relationship from the adolescent client’s perspective. Aim: This study explores how adolescent clients experience power in person-centred therapy relationships. Method: Seven adolescent clients in person-centred therapy took part in semi-structured interviews. Interpretative phenomenological analysis was used to explore the meaning they made of their experiences. Results: The adolescents’ experiences centred around five themes: 1) feeling my vulnerability entering a relationship with a powerful figure; 2) being invited to express myself; 3) evaluating if I can trust my counsellor; 4) feeling I’m in control in a relationship with boundaries; and 5) exercising my power in the relationship. Conclusions: Participants negotiated the dynamics of an unequal therapy relationship and drew on the power of their counsellor in coming to feel more empowered. Person-centred therapists need to recognise this inequality and use their power to help adolescent clients use the therapeutic space.